Revisión de estándares internacionales para la producción de plásticos Oxo-Biodegradables (2021)
The present degree work was developed with the main objective of examining the ASTM international standards that justify the biodegradation of oxo-biodegradable plastics, in this way to theoretically review if the Oxo-Biodegradable LDPE low-density polyethylene plastic bags comply with the results provided. by its manufacturers, who specify that it does not generate microplastic once discarded, thus reducing its accumulation in terrestrial and aquatic ecosystems.